MENDETEKSI TINGKAT KETAJAMAN SCANNER QR (QUICK RESPONSE CODE) UNTUK MASA KEDALUWARSA PRODUK KEMASAN MENGGUNAKAN FUZZY RULE BASE - Nuniek Herawati (IST AKPRIND Yogyakarta, 2018)
Many cases of sale of products that have not been qualified or have used up safely, so-called products that have expired. These events have an adverse effect on the community as consumers because they are the losers and sellers and producers will get complaints about their non-quality products. In addition, the use of products that have expired can have a negative impact on the health of consumers. . But on the other hand, supervision of the expiration of each product's active period is less noticed because of the difficulty in finding the expiration date on the packaging or the printed date has been lost, even though the packaging still looks good.The research was conducted to detect the validity period of a product using the Quick Response Code (QR Code) planted on a smartphone with a good camera feature (Miftah). Then to determine the sharpness level of detection will be used Fuzzy Rule Base with linguistic variables for scan and lighting distances.System test results are applied to convex bottles and flat plastic packaging, indicating that the application can scan the QR code. The sharpness level of the scanner uses a fuzzy rule base built from a distance of 1 cm to 20 cm with a 5 watt illumination of 0.5, while with a 10 watt illumination has a sharpness level of 0.6.